Advances in catching fruit butterflies for quick inventory - Maciel, Tatiane Tagliatti; Barbosa, Bruno Corrêa; Santos-Prezoto, Helba Helena; Aguiar, Jair Adriano; Prezoto, Fábio (Scientia Plena, 2020)
The family Nymphalidae comprises frugivorous butterflies that are frequently used as bioindicators in environmental assessment studies. The collection of these lepidopterans is easily made with traps filled with fruit baits. The most frequently used bait is a mixture of banana and sugarcane juice, though other mixtures are also attractive. Hence, the objective of the present study was to assess the attractiveness and aging effect of baits used to capture fruit-feeding butterflies. All tested baits contained fructose, glucose, and sucrose but it was not possible to determine an optimal capture period in terms of bait aging, as sugar concentrations varied throughout the fermentation process.